Net knee peak power output in four landing strategies after block in volleyball - Zahradnik, D.; Jandacka, D.; Farana, R.; Uchytil, J.; Zvonar, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
The maximal rate of energy absorption of the knee joint represents a risk factor in noncontact knee injuries. The aim of the study is to compare the absorbed net knee peak power during a bilateral landing after a block in a stick, balance, step back and run back landing strategies. Twelve male professional volleyball players of the highest caliber in the Czech Republic (aged 24.5 ± 4.6 years; height 196.8 ± 0.1 cm; mass 90.1 ± 8.3 kg) participated in this study. From the aspect of the absorbed net knee joint peak power, the landing strategy step back and stick landing appears to be the best option. The balance landing may be in greater risk of non-contact knee injuries.